The obligatory texts (yig-cha) for the study of Madhyamika of Byes Grwa-tshaṅ of Se-ra Monastery - Se-ra Rje-btsun Chos-kyi-rgyal-mtshan, 1469-1546 (Madhaymika text series, 1973)
Madhyamika philosophy according to the Gelukpa sect of Tibetan Buddhism; the textbooks used in Chay Colleg of Sera and affiliates.